Synthesis and crystal structure of slab perovskites SrLa1–xGdxScO4 - Titov, Y.A.; Slobodyanik, M.S.; Strutynska, N.Yu.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
The isovalent substitution conditions of lanthanum by gadolinium atoms in slab perovskite-like structure of SrLa1–xGdxScO4 (0 ≤ x ≤ 0. 8) scandates have defined. Orthorhombic (space group Abma) crystal structure of SrLa1–xGdxScO4 phases with the degree of lanthanum atoms substitution of 0. 2, 0. 4, 0. 6, and 0. 8 have determined using the Rietveld method. The main structural units of SrLa1–xGdxScO4 are two-dimensional perovskite-like blocks with a thickness of one slab of distorted ScO6 octahedra joined by vertices. Neighboring blocks are separated by the slab of (Sr, La, Gd)О9 polyhedra. There are no direct Sc—O—Sc bonds between the octahedra of adjacent blocks. Blocks are connected through —O—(Sr, La, Gd)—O— bonds. Analysis of the crystallochemical parameters of the synthesized phases has shown that, in the case of the isovalent substitution of lanthanum atoms by smaller gadolinium atoms in a slab structure of SrLa1–xGdxScO4, a gradual reduction of the length of (Sr, La, Gd)—О2 interblock bonds (from 0. 2378(7) nm at х = 0 up to 0. 230(1) nm at х = 0. 8) takes place. Reducing the distance between perovskite-like blocks brings the constitution of the two-dimensional slab perovskite-like structure SrLa1–xGdxScO4 closer to the structure of three-dimensional perovskite, which ultimately leads to its destruction at x > 0. 8 and gives the basis for the conclusion that this is the factor caused a limitation of area of SrLa1–xGdxScO4 (0 ≤ x ≤ 0. 8) solid solutions with slab perovskite-like structure and the absence of SrGdScO4 compound. The structural features of the slab structure of isovalently substituted samples of the SrLa1–xGdxScO4 and Sr1–xCaxLaScO4 systems are compared.